2011
DOI: 10.1093/geronb/gbr015
|View full text |Cite
|
Sign up to set email alerts
|

Visual Impairment and Quality of Life Among Older Adults: An Examination of Explanations for the Relationship

Abstract: By identifying multiple pathways through which visual impairment diminishes quality of life among older adults, this study highlights the importance of multipronged intervention efforts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
114
1
9

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(134 citation statements)
references
References 35 publications
5
114
1
9
Order By: Relevance
“…Two previous population-based longitudinal studies (Brown and Barrett, 2011;Chou, 2008) investigating specifically the effect of global vision loss on depressive symptoms found a positive association. In two-wave studies, the authors used a self-reported categorical assessment of global visual function with usual optical correction.…”
Section: Vision Loss As a Risk Factor For Depressive Symptomatologymentioning
confidence: 78%
See 2 more Smart Citations
“…Two previous population-based longitudinal studies (Brown and Barrett, 2011;Chou, 2008) investigating specifically the effect of global vision loss on depressive symptoms found a positive association. In two-wave studies, the authors used a self-reported categorical assessment of global visual function with usual optical correction.…”
Section: Vision Loss As a Risk Factor For Depressive Symptomatologymentioning
confidence: 78%
“…In two-wave studies, the authors used a self-reported categorical assessment of global visual function with usual optical correction. Brown et al (Brown and Barrett, 2011) did not exclude from the analysis participants presenting depressive symptoms at baseline, thus confounding the effects of baseline depression and baseline vision. However, by investigating possible mediating effects they observed that "psychological resources" (self-efficacy) and activity limitations to be two principal mediators.…”
Section: Vision Loss As a Risk Factor For Depressive Symptomatologymentioning
confidence: 99%
See 1 more Smart Citation
“…3,5 Visual impairment reduces QoL. 18,19 As such, it is reasonable to expect brow ptosis to have a negative effect on QoL, and corrective surgery to address this. In this study, we did not test visual fields after taping or manually elevating the eyelid because the results of the Federici study showed that taped/manually elevated VF measurements were not predictive of improvement in function after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…They may also become nervous because of feeling insecure and lost (Mirzaei, & Saeedi, 2013). Brown (2011) found out that severe visual disorders were associated with symptoms of depression and lower life satisfaction. These indicators have important roles in effects of vision disorder on reducing the quality of life, but their most important impact relates to self-efficacy.…”
Section: An Epidemiology Study Conducted In Tehran In 2007mentioning
confidence: 99%